APLIKASI PERPUSTAKAAN MENGGUNAKAN QUICK RESPONSE CODE - Yunus, Mughaffir; Adrisal (Fakultas Teknik Universitas Muhammadiyah Parepare, 2021)
With the development of technology makes people think to be able to work more effectively and efficiently. One of them is making a conventional system into a computerized system. Using a computerized system can make work easier because almost all computerized systems are systems that are ready to use.Therefore the use of information technology in the scope of the library in the village is not only as an automation process for information access, but also creates accuracy, speed, and completeness of an integrated system, so that the transaction process that occurs will be effective and efficient. Information Technology can also support the availability of integrated information in an effort to create various facilities in carrying out all transactions in the library, for example the process of registering new members, ordering collections, borrowing collections and returning library collections.Therefore, based on the above thought as well as evidence of adjustments to the development of information technology, this research will take the title of Library Application Using Online-Based Quick Response Code.